Potentiating pneumococcal glycoconjugate vaccine PCV13 with saponin adjuvant VSA-1 - Kim, Hyunjung; Yu, Jigui; Bai, Di; Nahm, Moon H.; Wang, Pengfei (Frontiers in Immunology, 2022)
VSA-1 is a semisynthetic saponin adjuvant prepared from naturally occurring Momordica saponin and capable of stimulating antigen-specific humoral and cellular immune responses. Its immunostimulating activity in enhancing the immune responses induced by the clinical glycoconjugate pneumococcal vaccine PCV13 is compared with QS-21 in female BALB/c mice. Both VSA-1 and QS-21 boosted IgG and opsonic antibodies titers against seven selected serotypes, including serotypes 3, 14, and 19A that are involved in most PCV13 breakthroughs. Since VSA-1 is much more accessible and of lower toxicity than QS-21, it can be a practical saponin immunostimulant to be included in a new glycoconjugate pneumococcal vaccine formulation.